LAYERED CATALYST COMPOSITIONS AND CATALYST ARTICLES AND METHODS OF MAKING AND USING SAME - Patent application
Patent Information
- Application Number
- JP2021536084
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-01-18
- Filing Date
- 2019-12-16
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2039-12-16
Smart Images

Figure 0007651459000004 
Figure 0007651459000005 
Figure 0007651459000006
Abstract
Description
[Technical field]
[0001] The invention as claimed relates to layered catalyst compositions and layered catalyst articles useful for treating exhaust gases to reduce pollutants contained therein. In particular, the invention as claimed relates to layered catalyst compositions and layered catalyst articles comprising platinum group metals and non-platinum group metals. [Background technology]
[0002] Various catalysts and catalyst systems are known for treating engine exhaust gases, which typically contain pollutants such as hydrocarbons (HC), carbon monoxide (CO), and nitrogen oxides (NOx). There is a need to substantially remove these pollutants from the exhaust gases to meet stringent government regulations. Three-way conversion (TWC) catalysts are typically utilized to treat exhaust gases emitted from gasoline-powered vehicles. TWC catalysts and related systems are based on platinum group metals (PGMs), such as platinum, palladium, and rhodium. Platinum group metal-based TWC catalysts are well known for effectively reducing pollutants from gasoline engines. However, because platinum group metals are expensive, there is a demand for the creation of TWC catalysts and systems that use reduced amounts of PGMs.
[0003] To meet such demand, various attempts have been made in the past, including replacing at least a portion of the PGMs with other metals, such as base metals, which are very cheap and available in large quantities. However, these catalysts and systems suffer from one or more drawbacks, including, but not limited to, lack of desirable efficiency for oxidizing HC and CO and reducing NOx, low thermal stability, etc. Thus, these catalysts still utilize large amounts of PGMs to achieve desirable efficiency, thereby preventing an overall cost reduction.
[0004] Furthermore, in some catalysts or systems, the addition of selected base metals to the catalyst has been found to result in poisoning by the PGMs, resulting in lower catalyst efficiency.
[0005] Thus, a need remains for catalyst compositions and / or catalyst articles that can significantly reduce the utilization of PGMs and thereby be cost-effective and highly efficient for removing HC, CO and NOx compounds from automotive exhaust sources to meet increasingly stringent regulations. Summary of the Invention
[0006] Therefore, in order to reduce platinum group metal utilization but achieve desirable or improved emission control functionality, the claimed invention focuses on providing catalyst compositions that include combinations of platinum group metals and non-platinum group metals.
[0007] In one aspect, the invention claimed is a layered catalyst article comprising: a) a first layer comprising a nickel component supported on a ceria component, the amount of the nickel component being 1.0 to 50 wt. %, calculated as nickel oxide, based on a total weight of the first layer, and the first layer being essentially free of copper, the amount of copper being <0.001 wt. %; b) a second layer comprising an oxygen storage component and a platinum group metal component supported on the alumina component, the platinum group metal component comprising platinum, rhodium, palladium, or any combination thereof, the amount of the platinum group metal component being 0.01 to 5 wt. %, based on the total weight of the second layer; and c) a substrate.
[0008] In yet another aspect, the claimed invention provides a process for preparing a layered catalyst article, the process comprising preparing a bottom layer slurry, depositing the bottom layer slurry on a substrate to obtain a bottom layer, preparing a top layer slurry, and depositing the top layer slurry on the bottom layer to obtain a top layer, followed by calcination at a temperature in the range of 400-700° C. Typically, the step of preparing the bottom layer slurry or the top layer slurry comprises a technique selected from incipient wetness impregnation, incipient wetness co-impregnation, and post-addition.
[0009] In yet another aspect, the claimed invention provides an exhaust system for an internal combustion engine, the system including a layered catalyst article.
[0010] In another aspect, the claimed invention provides a method for reducing the levels of hydrocarbons, carbon monoxide, and nitrogen oxides in a gaseous exhaust stream comprising contacting the gaseous exhaust stream with a catalytic article or an exhaust system according to the claimed invention to reduce the levels of hydrocarbons, carbon monoxide, and nitrogen oxides in the exhaust gas.
[0011] In another aspect, the claimed invention provides the use of a catalytic article for purifying a gaseous exhaust stream containing hydrocarbons, carbon monoxide, and nitrogen oxides. [Brief description of the drawings]
[0012] To provide an understanding of embodiments of the present invention, reference is made to the accompanying drawings, which are not necessarily drawn to scale, and in which reference numerals refer to components of exemplary embodiments of the present invention. The drawings are illustrative only and should not be construed as limiting the present invention. The above and other features of the claimed invention, their nature and various advantages will become more apparent from a consideration of the following detailed description in conjunction with the accompanying drawings.
[0013] [Figure 1]1 is a schematic diagram of an exemplary catalyst article design in a layered configuration according to different embodiments of the present invention. [Figure 2A] 1 is a schematic diagram of an exhaust system in accordance with one embodiment of the present invention; [Figure 2B] 2 is a schematic diagram of an exhaust system in accordance with another embodiment of the claimed invention. [Figure 2C] FIG. 2 is a schematic diagram of an exhaust system in accordance with yet another embodiment of the claimed invention. [Figure 3A] 1 is a perspective view of a honeycomb-type substrate support that may include a layered catalyst composition according to one embodiment of the claimed invention. [Figure 3B] 3B is a partial cross-sectional view enlarged compared to FIG. 3A and taken along a plane parallel to an end face of the substrate support of FIG. 3A, showing an enlarged view of a number of gas flow passages shown in FIG. 3A. [Figure 4] FIG. 3B is an enlarged cross-sectional cutaway view of the honeycomb-type substrate of FIG. 3A, representing a wall-flow filter substrate monolith. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The claimed invention is described more fully below. The claimed invention may be embodied in many different forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that the claimed invention will be thorough and complete, and will fully convey the scope of the invention to those skilled in the art. No language in the specification should be construed as indicating any non-claimed element as essential to the practice of the disclosed materials and methods.
[0015] In the context of describing the materials and methods discussed herein (particularly in the context of the claims which follow), the use of the terms "a," "an," "the," and similar directives are intended to cover both the singular and the plural, unless otherwise indicated in the specification or clearly contradicted by context.
[0016] All methods described herein can be performed in any suitable order unless otherwise stated herein or clearly contradicted by context. The use of any and all examples or exemplary language (e.g., "etc.") provided herein is intended only to better describe the materials and methods and no limitation of scope is asserted unless expressly stated.
[0017] As used herein, the term "catalyst" or "catalyst composition" refers to a material that promotes a reaction.
[0018] The term "NOx" refers to nitrogen oxide compounds such as NO or NO2.
[0019] As used herein, "non-PGM metals" refers to active metals or metal oxides including, but not limited to, Ni, Fe, Mn, Zn, and any mixtures thereof.
[0020] As used herein, the term "essentially free of copper" refers to no exogenous copper or copper oxide added to the first layer, however, optionally, may be present in trace amounts of <0.001%. Terms such as "exhaust stream", "engine exhaust stream", "exhaust gas stream" refer to any combination of flowing engine effluent gases, which may also contain solid or liquid particulate matter. The stream includes gaseous components, e.g., the exhaust of a lean-burn engine, and the exhaust stream of a lean-burn engine may contain certain non-gaseous components, such as liquid droplets, solid particulates, etc. The exhaust stream of a lean-burn engine typically further includes products of combustion, products of incomplete combustion, oxides of nitrogen, combustible and / or carbonaceous particulate matter (soot), and unreacted oxygen and / or nitrogen. Such terms refer to downstream effluents of one or more of the other catalyst system components described herein as well.
[0021] "BET surface area" has its usual meaning referring to the Brunauer-Emmett-Teller method for determining surface area by N2 adsorption measurements. Unless specifically stated otherwise, all references herein to "specific surface area" or "surface area" refer to BET surface area.
[0022] Platinum group metal (PGM) component refers to any component that includes a PGM (Rh, Pd, and Pt). For example, the PGM may be in a metallic form with a valence of zero, or the PGM may be in an oxide form. Reference to a "PGM component" allows for the presence of the PGM in any valence state. Terms such as "platinum (Pt) component," "rhodium (Rh) component," "palladium (Pd) component," and the like refer to the respective platinum group metal compounds, complexes, and the like that are decomposed or converted to a catalytically active form, typically a metal or metal oxide, upon calcination or use of the catalyst.
[0023] The term "catalytic article" or "catalyst article" refers to a component in which a substrate is coated with a catalyst composition used to promote a desired reaction. The term layered catalyst article refers to a catalyst article in which a substrate is coated in a layered manner with a PGM and / or non-PGM composition. These compositions may be referred to as washcoats.
[0024] As used herein, "impregnated" or "impregnation" refers to the infiltration of a catalytic material into the porous structure of a support material.
[0025] "Support" in the context of a catalytic material, or catalytic composition, or catalytic washcoat, refers to a material that receives metals (e.g., PGMs), stabilizers, promoters, binders, etc. through precipitation, association, dispersion, impregnation, or other suitable methods. Exemplary supports include the refractory metal oxide supports described herein below.
[0026] "Refractory metal oxide supports" are metal oxides including, for example, bulk alumina, ceria, zirconia, titania, silica, magnesia, neodymia, and other materials known for such use, as well as physical mixtures or chemical combinations thereof, including atomically doped combinations, and including active compounds such as high surface area or activated aluminas.
[0027] Exemplary combinations of metal oxides include alumina-zirconia, alumina-ceria-zirconia, lanthana-alumina, lanthana-zirconia-alumina, baria-alumina, baria-lanthana-alumina, baria-lanthana-neodymia alumina, and alumina-ceria. Exemplary aluminas include large pore boehmite, gamma-alumina, and delta / theta alumina. Useful commercially available aluminas used as starting materials in the exemplary process include activated aluminas such as high bulk density gamma-alumina, low or medium bulk density large pore gamma-alumina, and low bulk density large pore boehmite and gamma-alumina. Such materials are generally believed to provide durability to the resulting catalyst.
[0028] "High surface area refractory metal oxide support" refers specifically to support particles having pores greater than 20 Å and a broad pore distribution. High surface area refractory metal oxide supports, such as alumina support materials also referred to as "gamma alumina" or "activated alumina", typically have a surface area of 60 meters squared per gram ("m 2 / g), and in many cases up to about 300m 2 / g or more of virgin material. Such activated aluminas are typically mixtures of gamma and delta phases of alumina, but may also contain significant amounts of eta, kappa, and theta alumina phases.
[0029] As used herein, the term "oxygen storage component" (OSC) refers to an entity that has multiple valence states and can actively react with reducing agents such as carbon monoxide (CO) and / or hydrogen under reducing conditions and then react with oxidizing agents such as oxygen or nitrogen oxides under oxidizing conditions. Examples of oxygen storage components include ceria composites optionally doped with early transition metal oxides, particularly zirconia, lanthana, praseodymia, neodymia, niobia, europia, samaria, ytterbia, yttria, and mixtures thereof.
[0030] The claimed invention provides a layered catalyst article comprising: a) a first layer comprising a nickel component supported on a ceria component, the amount of the nickel component being 1.0-50 wt. % calculated as nickel oxide based on the total weight of the first layer, and the first layer being essentially free of copper, the amount of copper being <0.001 wt. %, b) a second layer comprising a platinum group metal component supported on an oxygen storage component and an alumina component, the platinum group metal component comprising platinum, rhodium, palladium, or any combination thereof, the amount of the platinum group metal component being 0.01-5 wt. % based on the total weight of the second layer, and c) a substrate, the first or second layer being deposited as a top or bottom layer on the substrate. In another embodiment, the amount of the platinum group metal component is 0.02-1.0 wt. % based on the total weight of the second layer. In another embodiment, the amount of the platinum group metal component is 0.02-0.1 wt.%, based on the total weight of the second layer. In one embodiment, the platinum group metal component comprises palladium and rhodium, and the ratio of palladium to rhodium ranges from 100:1 to 1:5. In another embodiment, the platinum group metal component comprises platinum and rhodium, and the ratio of platinum to rhodium ranges from 100:1 to 1:5. In yet another embodiment, the platinum group metal component is rhodium, and the amount of rhodium is 0.02-1.0 wt.%, based on the total weight of the second layer.
[0031] The catalyst composition takes advantage of the high efficiency of precious metals such as PGMs and the low cost of non-PGM metals such as base metals. The combination of both precious metals and non-PGM catalyst components works effectively and synergistically for efficient CO, NOx, and HC conversion and reduction of pollutants contained in the exhaust gas stream.
[0032] In one embodiment, the layered catalyst article includes: a) a first layer comprising a nickel component supported on a ceria component, the amount of the nickel component being 10-40 wt. %, calculated as nickel oxide, based on a total weight of the first layer, and the first layer being essentially free of copper; b) a second layer comprising an oxygen storage component and a platinum group metal component supported on an alumina component, the platinum group metal component comprising platinum, rhodium, palladium, or any combination thereof, and the amount of the platinum group metal component being 0.01-5 wt. %, based on a total weight of the second layer; and c) a substrate, wherein the first or second layer is deposited as a top or bottom layer on the substrate.
[0033] In another embodiment, a layered catalyst article includes: a) a first layer comprising a nickel component supported on a ceria component, wherein the amount of the nickel component is 10 to 40 wt. %, calculated as nickel oxide, based on a total weight of the first layer, and the first layer is essentially free of copper; b) a second layer comprising a platinum group metal component supported on an oxygen storage component and an alumina component, wherein the platinum group metal component comprises platinum, rhodium, palladium, or any combination thereof, and the amount of the platinum group metal component is 0.02 to 1.0 wt. %, based on a total weight of the second layer; and c) a substrate, wherein the first or second layer is deposited as a top or bottom layer on the substrate.
[0034] In another embodiment, a layered catalyst article includes: a) a first layer comprising a nickel component supported on a ceria component, wherein the amount of the nickel component is 10 to 40 wt. %, calculated as nickel oxide, based on a total weight of the first layer, and the first layer is essentially free of copper; b) a second layer comprising an oxygen storage component and a platinum group metal component supported on an alumina component, wherein the platinum group metal component comprises platinum, rhodium, palladium, or any combination thereof, and the amount of the platinum group metal component is 0.02 to 0.1 wt. %, based on a total weight of the second layer; and c) a substrate, wherein the first or second layer is deposited as a top or bottom layer on the substrate.
[0035] In one embodiment, the layered catalyst article is: a) calcined at 950° C. for 12 hours in air, followed by 15 minutes of 2 / g~60m 2 a) a first layer comprising a nickel component supported on a ceria component comprising ceria having a specific surface area in the range of 0.1 to 1.5 wt. %, calculated as nickel oxide, based on a total weight of the first layer, the amount of the nickel component being 1.0 to 50 wt. %, calculated as nickel oxide, based on the total weight of the first layer, the amount of the ceria component being 20 to 80 wt. %, based on the total weight of the first layer, and the first layer being essentially free of copper; b) a second layer comprising a platinum group metal component supported on an oxygen storage component and an alumina component, the platinum group metal component comprising platinum, rhodium, palladium, or any combination thereof, the amount of the platinum group metal component being 0.01 to 5 wt. %, based on the total weight of the second layer; and c) a substrate, wherein the first or second layer is deposited as a top or bottom layer on the substrate.
[0036] In one embodiment, the ceria component of the first layer includes a dopant. Examples of dopants include, but are not limited to, zirconia, yttria, praseodymia, lanthana, neodymia, samaria, gadolinia, alumina, titania, baria, strontia, and combinations thereof. The dopant is used in an amount of 1.0 to 20 wt. %, based on the total weight of the ceria component. In one embodiment, the layered catalyst article is a) calcined at 950° C. for 12 hours in air, followed by 15 min. 2 / g~60m 2 a first layer comprising a nickel component supported on a ceria component comprising ceria having a specific surface area in the range of 0.1 to 1.5 μm / g, and a dopant selected from zirconia, yttria, praseodymia, lanthana, neodymia, samaria, gadolinia, alumina, titania, baria, strontia, and combinations thereof, wherein the amount of the nickel component is 1.0 to 50 wt. %, calculated as nickel oxide, based on the total weight of the first layer, and the amount of the ceria component is 20 to 80 wt. %, based on the total weight of the first layer, and the amount of the dopant is 0.1 to 1.5 wt. %, calculated as nickel oxide, based on the total weight of the first layer. % based on the total weight of the ceria component, the first layer being essentially free of copper; b) a second layer comprising a platinum group metal component supported on the oxygen storage component and the alumina component, the platinum group metal component comprising platinum, rhodium, palladium, or any combination thereof, the platinum group metal component having an amount of 0.01 to 5 wt %, based on the total weight of the second layer; and c) a substrate, wherein the first or second layer is deposited as a top or bottom layer on the substrate.
[0037] In one embodiment, the layered catalyst article is: a) calcined at 950° C. for 12 hours in air; 2 / g~60m 21. A first layer comprising: a nickel component supported on a ceria component comprising ceria having a specific surface area in the range of 0.1 to 1.5 μm / g; and optionally a dopant selected from zirconia, yttria, praseodymia, lanthana, neodymia, samaria, gadolinia, alumina, titania, baria, strontia, and combinations thereof; and ii) a transition metal selected from manganese, iron, zinc, and combinations thereof, wherein the amount of the nickel component is 1.0 to 50 wt. %, calculated as nickel oxide, based on the total weight of the first layer; the amount of the ceria component is 20 to 80 wt. %, based on the total weight of the first layer; and the amount of the dopant is % based on the total weight of the ceria component and the amount of the transition metal, calculated as the corresponding transition metal oxide, is 1.0-10 wt %, based on the total weight of the first layer, the first layer being essentially free of copper; b) a second layer comprising a platinum group metal component supported on an oxygen storage component and an alumina component, the platinum group metal component comprising platinum, rhodium, palladium, or any combination thereof, and the amount of the platinum group metal component is 0.01-5 wt %, based on the total weight of the second layer; and c) a substrate, wherein the first or second layer is deposited as a top or bottom layer on the substrate.
[0038] In one embodiment, the layered catalyst article is: a) calcined at 950° C. for 12 hours in air; 2 / g~60m 2a nickel component supported on a ceria component comprising ceria having a specific surface area in the range of 0.1 to 1.5 μm / g, and optionally a dopant selected from zirconia, yttria, praseodymia, lanthana, neodymia, samaria, gadolinia, alumina, titania, baria, strontia, and combinations thereof, and ii) iron, wherein the amount of the nickel component is 1.0 to 50 wt. %, calculated as nickel oxide, based on the total weight of the first layer, the amount of the ceria component is 20 to 80 wt. %, based on the total weight of the first layer, and the amount of the dopant is 0.1 to 0.5 wt. %, calculated as nickel oxide, based on the total weight of the first layer, and % based on the total weight of the first layer, the amount of iron being 1.0 to 20 wt. %, calculated as iron oxide, based on the total weight of the first layer, the first layer being essentially free of copper; b) a second layer comprising a platinum group metal component supported on an oxygen storage component and an alumina component, the platinum group metal component comprising platinum, rhodium, palladium, or any combination thereof, the amount of the platinum group metal component being 0.01 to 5 wt. %, based on the total weight of the second layer; and c) a substrate, wherein the first or second layer is deposited as a top or bottom layer on the substrate.
[0039] In yet another embodiment, the first layer includes a transition metal other than nickel. The transition metals used include, but are not limited to, manganese, iron, zinc, and combinations thereof. In one embodiment, the amount of transition metal used is 1.0-10 wt. %, calculated as the corresponding transition metal oxide, based on the total weight of the first layer. In one embodiment, the transition metal is iron and is used in an amount of 1.0-10 wt. %, calculated as iron oxide, based on the total weight of the first layer. In one embodiment, the layered catalyst article is a) calcined at 950° C. for 12 hours in air, followed by 15 min. 2 / g~60m 2a) a nickel component supported on a ceria component comprising ceria having a specific surface area in the range of 0.1 to 1.5 μm / g, and optionally a dopant selected from zirconia, yttria, praseodymia, lanthana, neodymia, samaria, gadolinia, alumina, titania, baria, strontia, and combinations thereof, and ii) optionally a transition metal selected from manganese, iron, and zinc, wherein the amount of the nickel component is 1.0 to 50 wt. %, calculated as nickel oxide, based on a total weight of the first layer, the amount of the ceria component is 20 to 80 wt. %, based on a total weight of the first layer, the amount of the dopant is 1.0 to 20 wt. %, based on a total weight of the ceria component, and the amount of the transition metal is a corresponding transition metal, calculated as nickel oxide, based on a total weight of the first layer. %. The method of claim 1, further comprising: (a) depositing a first layer having a copper content of 1.0-10 wt. %, calculated as metal oxide, and the first layer being essentially free of copper; and (b) depositing a second layer having a copper content of 1.0-10 wt. %, calculated as metal oxide, and the first layer being essentially free of copper; and (c) depositing a second layer having a copper content of 1.0-10 wt. %, calculated as metal oxide, and the first layer being essentially free of copper; and (d) depositing a second layer having a copper content of 1.0-10 wt. %, calculated as metal oxide, and the first layer being essentially free of copper; and
[0040] In one embodiment, the layered catalyst article is: a) calcined at 950° C. for 12 hours in air; 2 / g~60m 2a nickel component supported on a ceria component comprising ceria having a specific surface area in the range of 1.0 to 50 wt. %, calculated as nickel oxide, based on a total weight of the first layer, and a dopant selected from zirconia, yttria, praseodymia, lanthana, neodymia, samaria, gadolinia, alumina, titania, baria, strontia, and combinations thereof; and ii) optionally a transition metal selected from manganese, iron, zinc, and combinations thereof, wherein the amount of the nickel component is 1.0 to 50 wt. %, calculated as nickel oxide, based on a total weight of the first layer, the amount of the ceria component is 20 to 80 wt. %, based on a total weight of the first layer, and the amount of the dopant is 1.0 to 20 wt. %, based on a total weight of the ceria component. %, calculated as the corresponding transition metal oxide, based on the total weight of the first layer, and the amount of alkaline earth metal oxide is 1.0-10 wt. %, calculated as the corresponding transition metal oxide, based on the total weight of the first layer, and the first layer is essentially free of copper; b) a second layer comprising: i) rhodium in an amount of 0.02-1.0 wt. %, based on the total weight of the second layer, supported on an oxygen storage component and an alumina component, and ii) optionally at least one alkaline earth metal oxide comprising barium oxide, strontium oxide, or any combination thereof; and c) a substrate, wherein the first or second layer is deposited as a top or bottom layer on the substrate.
[0041] In one embodiment, the layered catalyst article comprises: i) a nickel component; ii) a catalyst composition comprising: 2 / g~60m 2a ceria component comprising ceria having a specific surface area in the range of 0.1 to 1.5 wt. % based on the total weight of the first layer, calculated as nickel oxide; and optionally a dopant selected from zirconia, yttria, praseodymia, lanthana, neodymia, samaria, gadolinia, alumina, titania, baria, strontia, and combinations thereof; and iii) optionally a transition metal selected from manganese, iron, zinc, and combinations thereof, wherein the amount of the nickel component is 1.0 to 50 wt. %, calculated as nickel oxide, based on the total weight of the first layer, the amount of the ceria component is 20 to 80 wt. %, based on the total weight of the first layer, and the amount of the dopant is 0.1 to 1.5 wt. %, calculated as nickel oxide, based on the total weight of the first layer, and , 1.0-20 wt. %, and the amount of transition metal, calculated as the corresponding transition metal oxide, is 1.0-10 wt. %, based on the total weight of the first layer, the first layer being essentially free of copper; b) a second layer comprising i) palladium and rhodium, wherein the ratio of palladium or platinum to rhodium is in the range of 100:1 to 1:5, ii) an oxygen storage component, iii) an alumina component, and iv) optionally at least one alkaline earth metal oxide comprising barium oxide, strontium oxide, or any combination thereof; and c) a substrate, wherein the first or second layer is deposited as a top or bottom layer on the substrate.
[0042] In one embodiment, the layered catalyst article is: a) calcined at 950° C. for 12 hours in air; 2 / g~60m 2a) a nickel component supported on a ceria component comprising ceria having a specific surface area in the range of 0.1 to 1.5 μm / g, and optionally a dopant selected from zirconia, yttria, praseodymia, lanthana, neodymia, samaria, gadolinia, alumina, titania, baria, strontia, and combinations thereof, and ii) optionally a transition metal selected from manganese, iron, zinc, and combinations thereof, wherein the amount of the nickel component is 1.0 to 50 wt. %, calculated as nickel oxide, based on a total weight of the first layer, and the amount of the ceria component is 20 to 80 wt. %, based on a total weight of the first layer, and the amount of the dopant is 0.1 to 1.5 wt. %, calculated as nickel oxide, based on a total weight of the first layer, and and the amount of transition metal is 1.0 to 20 wt. %, calculated as the corresponding transition metal oxide, based on the total weight of the first layer, and the first layer is essentially free of copper; b) a second layer comprising i) palladium and rhodium, with a ratio of palladium or platinum to rhodium in the range of 100:1 to 1:5, supported on an oxygen storage component and an alumina component, and ii) optionally at least one alkaline earth metal oxide comprising barium oxide, strontium oxide, or any combination thereof; and c) a substrate, wherein the first or second layer is deposited as a top or bottom layer on the substrate.
[0043] Exemplary oxygen storage components include ceria-zirconia, ceria-zirconia-lanthana, ceria-zirconia-yttria, ceria-zirconia-lanthana-yttria, ceria-zirconia-neodymia, ceria-zirconia-praseodymia, ceria-zirconia-lanthana-neodymia, ceria-zirconia-lanthana-praseodymia, ceria-zirconia-lanthana-neodymia-praseodymia, or combinations thereof. In one embodiment, the oxygen storage component comprises ceria-zirconia. In one embodiment, the amount of oxygen storage component is 20-80 wt.% based on the total weight of the second layer. In one embodiment, the ceria content of the oxygen storage component of the second layer ranges from 5-50 wt.% based on the total weight of the oxygen storage component. In one embodiment, the ceria component present in the first layer is 0.1% by weight after calcination in air at 950° C. for 12 hours. 2 / g~60m 2 The first layer includes a ceria having a specific surface area in the range of 0.1 to 1.0 μm / g, and the amount of the ceria component used is 20 to 80 wt % based on the total weight of the first layer. In another embodiment, the ceria component of the first layer includes a dopant. Examples of dopants include, but are not limited to, zirconia, yttria, praseodymia, lanthana, neodymia, samaria, gadolinia, alumina, titania, baria, strontia, and combinations thereof. The dopant is used in an amount of 1.0 to 20 wt % based on the total weight of the ceria component.
[0044] In one embodiment, the alumina component comprises alumina, lanthana-alumina, ceria-alumina, ceria-zirconia-alumina, zirconia-alumina, lanthana-zirconia-alumina, baria-alumina, baria-lanthana-alumina, baria-lanthana-neodymia-alumina, or combinations thereof, In one embodiment, the amount of the alumina component is in the range of 10 to 80 wt %, based on the total weight of the second layer.
[0045] As used herein, the term "substrate" refers to a monolithic material, typically in the form of a washcoat containing a plurality of particles containing a catalyst composition, on which the catalyst material is disposed.
[0046] References to a "monolithic substrate" or a "honeycomb substrate" mean a unitary structure that is homogenous and continuous from the inlet to the outlet.
[0047] As used herein, the term "washcoat" has its ordinary meaning in the art of a thin, adherent coating of catalyst or other material applied to a substrate material, such as a honeycomb-type support member, that is sufficiently porous to permit the passage of the gas stream to be treated.
[0048] The washcoat is formed by preparing a slurry containing particles of a certain solids content (e.g., 20% to 60% by weight) in a liquid vehicle, which is then coated onto the substrate and dried to provide a washcoat layer.
[0049] As used herein and as described in Heck, Ronald and Farrauto, Robert, Catalytic Air Pollution Control, New York: Wiley-Interscience, 2002, pp. 18-19, a washcoat layer includes a layer of compositionally distinct material deposited on the surface of a monolithic substrate, or an underlying washcoat layer. In one embodiment, the substrate contains one or more washcoat layers, each of which may differ in some manner (e.g., in its physical properties, such as particle size or crystallite phase, for example) and / or may differ in chemical catalytic function.
[0050] A catalyst product may be "virgin," meaning that it is new and has not been exposed to heat or thermal stress for an extended period of time. "Virgin" may also mean that the catalyst has been recently prepared and has not been exposed to exhaust gases or high temperatures. Similarly, an "aged" catalyst article is not virgin, but has been exposed to exhaust gases and high temperatures (i.e., greater than 500° C.) for an extended period of time (i.e., greater than 3 hours).
[0051] According to one or more embodiments, the substrate of the claimed catalyst article of the invention may be constructed of any material typically used to prepare automotive catalysts, and typically includes ceramic or metallic monolithic honeycomb structures. The substrate typically provides a multi-wall surface to which a washcoat comprising the catalyst composition described hereinabove is applied and adhered, thereby acting as a support for the catalyst composition.
[0052] Exemplary metallic substrates include metal alloys such as heat-resistant metals, titanium and stainless steel, as well as other alloys in which iron is a substantial or major component. Such alloys may contain one or more of nickel, chromium, and / or aluminum, and the amount of these metals may advantageously comprise at least 15% by weight of the alloy, for example, 10-25% chromium, 3-8% aluminum, and up to 20% nickel by weight. The alloys may also contain small or trace amounts of one or more metals, such as manganese, copper, vanadium, titanium, etc. The surface of the metal substrate may be oxidized at high temperatures, for example, 1000° C. or higher, to form an oxide layer on the surface of the substrate, which may improve the corrosion resistance of the alloy and facilitate adhesion of a washcoat layer to the metal surface.
[0053] The ceramic material used to construct the substrate can include any suitable refractory material, such as cordierite, mullite, cordierite-alumina, silicon nitride, zircon-mullite, spodumene, alumina-silica magnesia, zircon silicate, sillimanite, magnesium silicate, zircon, petalite, alumina, aluminosilicate, and the like. Any suitable substrate can be used, such as a monolithic flow-through substrate, having a plurality of fine, parallel gas flow passages extending from the inlet surface to the outlet surface of the substrate such that the passages are open for fluid flow. The passages, which are essentially straight-line paths from the inlet to the outlet, are defined by walls, and the catalytic material on the walls is coated as a washcoat, such that the gas flowing through the passages contacts the catalytic material. The flow passages of the monolithic substrate are thin-walled channels of any suitable cross-sectional shape, such as trapezoidal, rectangular, square, sinusoidal, hexagonal, elliptical, circular, and the like. Such structures contain from about 60 to about 1200 or more gas inlet openings (i.e., "cells") per square inch of cross section (cpsi), more typically from about 300 to 600 cpsi. The wall thickness of the flow-through substrate can vary, with a typical range being 0.002 to 0.1 inches. A representative commercially available flow-through substrate is a cordierite substrate having 400 cpsi and a 6 mil wall thickness, or 600 cpsi and a 4 mil wall thickness. However, it will be understood that the invention is not limited to a particular substrate type, material, or shape. In an alternative embodiment, the substrate can be a wall-flow substrate, with each passageway blocked at one end of the substrate body with a non-porous plug, and every other passageway blocked at the opposing end face. This requires that the gas flow through the porous walls of the wall-flow substrate to reach the outlet. Such monolithic substrates can contain up to about 700 or more cpsi, such as from about 100 to 400 cpsi, more typically from about 200 to about 300 cpsi. The cross-sectional shape of the cells can vary as described above. Wall flow substrates typically have wall thicknesses of 0.002 to 0.1 inches.A representative commercially available wall flow substrate is constructed from microporous cordierite, with exemplary microporous cordierite having a wall thickness of 200 cpsi and 10 mils or 300 cpsi and 8 mils, and a wall porosity of 45-65%. Other ceramic materials such as aluminum titanate, silicon carbide, and silicon nitride are also used as wall flow filter substrates. However, it will be understood that the present invention is not limited to a particular substrate type, material, or shape. It should be noted that when the substrate is a wall flow substrate, the catalyst composition, in addition to being disposed on the surface of the wall, may permeate the porous walls of the porous structure (i.e., may partially or completely close the porosity openings). In one embodiment, the substrate has a flow through ceramic honeycomb structure, a wall flow ceramic honeycomb structure, or a metal honeycomb structure.
[0054] In one exemplary embodiment, a first layer is deposited on a substrate as a bottom layer and a second layer is deposited on the bottom layer as a top layer (FIG. 1).
[0055] In another embodiment, the second layer is deposited as a bottom layer on the substrate and the first layer is deposited as a top layer on the bottom layer (FIG. 1).
[0056] In another embodiment, a layered catalyst article includes: a) a first layer comprising a nickel component and a ceria component, wherein the amount of the nickel component is 10 to 40 wt. %, calculated as nickel oxide, based on a total weight of the first layer, and the first layer is essentially free of copper; b) a second layer comprising a platinum group metal component, an oxygen storage component, and an alumina component, wherein the platinum group metal component comprises platinum, rhodium, palladium, or any combination thereof, and the amount of the platinum group metal component is 0.01 to 5 wt. %, based on a total weight of the second layer; and c) a substrate, wherein the first is deposited as a bottom layer on the substrate and the second layer is deposited as a top layer on the first layer.
[0057] In another embodiment, a layered catalyst article includes: a) a first layer comprising a nickel component and a ceria component, wherein the amount of the nickel component is 10 to 40 wt. %, calculated as nickel oxide, based on a total weight of the first layer, and the first layer is essentially free of copper; b) a second layer comprising a platinum group metal component, an oxygen storage component, and an alumina component, wherein the platinum group metal component comprises platinum, rhodium, palladium, or any combination thereof, and the amount of the platinum group metal component is 0.02 to 1.0 wt. %, based on a total weight of the second layer; and c) a substrate, wherein the second layer is deposited as a bottom layer on the substrate and the first layer is deposited as a top layer on the second layer. In one exemplary embodiment, a layered catalyst article includes a first layer including nickel impregnated in a ceria component and a second layer including rhodium impregnated in a ceria-zirconia and alumina component, the first layer being deposited on a substrate and the second layer being deposited on the first layer.
[0058] In another exemplary embodiment, a layered catalyst article includes a first layer including nickel impregnated in a ceria-zirconia-alumina component and a second layer including rhodium impregnated in a ceria-zirconia and alumina component, the first layer being deposited on a substrate and the second layer being deposited on the first layer.
[0059] In yet another exemplary embodiment, a layered catalyst article includes a first layer comprising nickel impregnated in ceria-zirconia-alumina and a second layer comprising palladium impregnated in ceria-zirconia and rhodium impregnated in an alumina component, the first layer being deposited on a substrate and the second layer being deposited on the first layer.
[0060] In another embodiment, the layered catalyst article includes a third layer comprising a platinum group metal component, an oxygen storage component, and an alumina component, wherein the platinum group metal component comprises platinum, rhodium, palladium, or any combination thereof, and the amount of the platinum group metal component is 0.01 to 5 wt. %, based on the total weight of the third layer.
[0061] In one embodiment, the layered catalyst article includes a first layer including a nickel component deposited on a substrate, a second layer including palladium deposited on the first layer, and a third layer including rhodium deposited on the second layer.
[0062] In one embodiment, the layered catalyst article described herein above comprises a zoned arrangement, the zoned arrangement consisting of a front zone (first zone) and a rear zone (second zone). In one embodiment, the layered catalyst article includes: a) a first layer comprising a nickel component supported on a ceria component, the amount of the nickel component being 10-40 wt. %, calculated as nickel oxide, based on a total weight of the first layer, the first layer being essentially free of copper; b) a second layer comprising a platinum group metal component supported on an oxygen storage component and an alumina component, the platinum group metal component comprising platinum, rhodium, palladium, or any combination thereof, the platinum group metal component being in an amount of 0.01-5 wt. %, based on a total weight of the second layer; and c) a substrate, the first or second layer being deposited as a top or bottom layer on the substrate, at least one of the first and second layers comprising a banded arrangement including a first zone and a second zone, the first or second zone spanning 45-90% of a length of the substrate.
[0063] In one embodiment, the first layer includes a front zone (first zone) or a rear zone (second zone), the front or rear zone spanning 45-90% of the length of the substrate. In another embodiment, the second layer includes a front zone (first zone) or a rear zone (second zone), the front or rear zone spanning 45-90% of the length of the substrate. In yet another embodiment, the third layer includes a front zone or a rear zone, the front or rear zone spanning 45-90% of the length of the substrate.
[0064] As used herein, the term "stream" broadly refers to any combination of flowing gases that may contain solid or liquid particulate matter.
[0065] As used herein, the terms "upstream" and "downstream" refer to relative directions relative to the flow of engine exhaust gas stream from the engine toward the tailpipe, with the engine being in the upstream position and the tailpipe and any pollution abatement articles, such as filters and catalysts, being downstream of the engine.
[0066] 3A and 3B show an exemplary substrate 2 in the form of a flow-through substrate coated with a washcoat composition described herein. Referring to FIG. 3A, the exemplary substrate 2 has a cylindrical and cylindrical outer surface 4, an upstream end surface 6, and a corresponding downstream end surface 8 that is identical to the end surface 6. The substrate 2 has a plurality of fine parallel gas flow passages 10 formed therein. As seen in FIG. 3B, the flow passages 10 are formed by walls 12 and extend through the substrate 2 from the upstream end surface 6 to the downstream end surface 8, the passages 10 being unobstructed and allowing a fluid, e.g., gas flow, to flow longitudinally through the substrate 2 via the gas flow passages 10. As can be more easily seen in FIG. 3, the walls 12 are dimensioned and configured such that the gas flow passages 10 have a substantially regular polygonal shape. As shown, the washcoat composition may be applied in multiple separate layers, if desired. In the embodiment shown, the washcoat consists of a first separate washcoat layer 14 adhered to the wall 12 of the substrate member and a second separate washcoat layer 16 coated over the first washcoat layer 14. In one embodiment, the claimed invention may also be practiced with two or more (e.g., three or four) washcoat layers and is not limited to the two-layer embodiment shown.
[0067] FIG. 4 shows an exemplary substrate 2 in the form of a wall-flow filter substrate coated with a washcoat composition described herein. As seen in FIG. 4, the exemplary substrate 2 has a plurality of passages 52. The passages are tubularly surrounded by the inner wall 53 of the filter substrate. The substrate has an inlet end 54 and an outlet end 56. The alternate passages are blocked at the inlet end with an inlet plug 58 and at the outlet end with an outlet plug 60 to form an opposing checkerboard pattern at the inlet 54 and outlet 56. Gas flow 62 enters through the unblocked channel inlet 64, is stopped by the outlet plug 60, and diffuses through the channel wall 53 (which is porous) to the outlet side 66. The gas is prevented from returning to the inlet side wall by the inlet plug 58. The porous wall-flow filters used in the present invention have catalysis in the walls of the element having or containing one or more catalytic materials on or within it. The catalytic material may be present on the walls of the element on the inlet side only, on the outlet side only, on both the inlet and outlet sides, or the walls themselves may consist entirely or in part of the catalytic material. The present invention includes the use of one or more layers of catalytic material on the inlet and / or outlet walls of the element.
[0068] According to yet another aspect, the claimed invention provides a process for preparing a layered catalyst article, the process comprising the steps of:
[0069] In the first step, a bottom layer slurry is prepared, which is then deposited on the substrate. Separately, a top layer slurry is prepared and deposited on the bottom layer, followed by calcination at a temperature in the range of 400-700°C. The steps of preparing the bottom and top layers include techniques such as incipient wetness impregnation, incipient wetness co-impregnation, and post-addition. In one embodiment, the process includes calcining the substrate coated with the bottom layer, followed by coating with the top layer. Typically, the calcination is carried out at a temperature in the range of 400-700°C.
[0070] Incipient wetness impregnation technique, also called capillary impregnation or dry impregnation, is usually used for the synthesis of heterogeneous materials, i.e. catalysts. Typically, active metal precursors are dissolved in an aqueous or organic solution, and then the metal-containing solution is added to the catalyst support, which contains a pore volume equal to the volume of the added solution. Capillary action draws the solution into the pores of the support. The solution added beyond the pore volume of the support results in a change in solution transport from a capillary action process to a much slower diffusion process. The catalyst is dried and calcined to remove the volatile components in the solution and deposit the metal on the surface of the catalyst support. The concentration profile of the impregnated material depends on the mass transfer conditions in the pores during impregnation and drying. After appropriate dilution, multiple active metal precursors can be co-impregnated into the catalyst support. Alternatively, the active metal precursors are introduced into the slurry via post-addition under stirring during the process of slurry preparation.
[0071] The support particles are typically dry enough to absorb substantially all of the solution to form a wet solid. Typically, an aqueous solution of a water-soluble compound or complex of the active metal, such as rhodium chloride, rhodium nitrate, rhodium acetate, or combinations thereof (if rhodium is the active metal), and palladium nitrate, palladium tetraamine, palladium acetate, or combinations thereof (if palladium is the active metal), is utilized. Following treatment of the support particles with the active metal solution, the particles are dried and then calcined to convert the active metal to a more catalytically active form, such as by heat treating the particles at an elevated temperature (e.g., 100-150°C) for a period of time (e.g., 1-3 hours). An exemplary calcination process includes heat treating in air at a temperature of about 400-550°C for 10 minutes to 3 hours. The above process can be repeated as necessary to reach the desired active metal impregnation level.
[0072] The catalyst composition is typically prepared in the form of catalyst particles as described above. These catalyst particles are mixed with water to form a slurry for the purpose of coating a catalyst substrate, such as a honeycomb-type substrate. In addition to the catalyst particles, the slurry may optionally contain a binder in the form of alumina, silica, zirconium acetate, colloidal zirconia, or zirconium hydroxide, an associative thickener, and / or a surfactant, including anionic, cationic, nonionic, or amphoteric surfactants. Other exemplary binders include boehmite, gamma-alumina, or delta / theta alumina, as well as silica sol. When present, the binder is typically used in an amount of about 1-5 wt.% of the total washcoat loading. The addition of acidic or basic species to the slurry is performed to adjust the pH accordingly. For example, in some embodiments, the pH of the slurry is adjusted by the addition of ammonium hydroxide, aqueous nitric acid, or acetic acid. A typical pH range for the slurry is about 3-12.
[0073] The slurry may be milled to reduce particle size and improve particle mixing. Milling may be accomplished in a ball mill, continuous mill, or other similar equipment, and the solids content of the slurry may be, for example, about 20-60% by weight, more specifically about 20-40% by weight. In one embodiment, the slurry after milling has a D of about 10 to about 40 microns, preferably 10 to about 30 microns, and more preferably about 10 to about 15 microns. 90 Characterized by particle size. D 90 is determined using a dedicated particle size analyzer. The instrument used in this example uses laser diffraction to measure particle size in a small amount of slurry. Typically, D in microns is 90 means that the number of particles has a diameter smaller than that value is 90%.
[0074] The slurry is coated onto the catalytic substrate using any washcoat technique known in the art. In one embodiment, the catalytic substrate is dipped or coated with the slurry one or more times. The coated substrate is then dried at an elevated temperature (e.g., 100-150°C) for a period of time (e.g., 10 minutes to 3 hours) and then calcined by heating, for example, at 400-700°C, typically for about 10 minutes to about 3 hours. Following drying and calcination, the final washcoat coating layer is considered to be essentially free of solvent. After calcination, the catalyst loading obtained by the above washcoat technique can be determined through calculating the difference between the coated and uncoated weights of the substrate. As will be apparent to one skilled in the art, the catalyst loading can be altered by modifying the rheology of the slurry. In addition, the coating / drying / calcining process to produce a washcoat can be repeated as necessary to build up the coating to a desired loading level or thickness, meaning that two or more washcoats can be applied.
[0075] In certain embodiments, the coated substrate is aged by subjecting the coated substrate to a heat treatment. In one embodiment, aging is performed at a temperature of about 850° C. to about 1050° C. in air with ambient moisture by volume for 20 hours. In certain embodiments, an aged catalyst article is thus provided. In certain embodiments, particularly useful materials include metal oxide-based supports (including but not limited to substantially 100% ceria supports) that retain a high percentage of their pore volume (e.g., about 95-100%) upon aging (e.g., about 850° C. to about 1050° C., 10% moisture by volume in air, aging for 20 hours).
[0076] In another aspect, the claimed invention provides an exhaust system for an internal combustion engine comprising a layered catalyst article comprising the layered catalyst composition described herein above. In one embodiment, the exhaust system comprises a layered catalyst article comprising: a first layer comprising a nickel component and a ceria component, wherein the amount of the nickel component is 1.0-50 wt. %, calculated as nickel oxide, based on the total weight of the first layer, and the first layer is essentially free of copper; a second layer comprising a platinum group metal component, an oxygen storage component, and an alumina component, wherein the platinum group metal component comprises platinum, rhodium, palladium, or any combination thereof, and the amount of the platinum group metal component is 0.01-5 wt. %, based on the total weight of the second layer; and a substrate.
[0077] In one embodiment, the exhaust system comprises a platinum group metal selected from platinum, palladium, rhodium, and combinations thereof, in an amount of 50 to 300 g / ft 3 2A and 2B show representative exhaust systems in which a conventional PGM-TWC catalyst article (C-TWC) and the claimed inventive layered catalyst article (PGM+non-PGM, inventive catalyst-IC) are located at different positions relative to the engine.
[0078] In one embodiment, a system includes a platinum group metal based three-way conversion (TWC) catalyst article and a layered catalyst article as described herein above, wherein the platinum group metal based three-way conversion (TWC) catalyst article is located downstream of an internal combustion engine and a catalyst article comprising the layered catalyst composition is located downstream in flow communication with the three-way conversion (TWC) catalyst article.
[0079] In another embodiment, a system includes a platinum group metal based three-way conversion (TWC) catalyst article and a layered catalyst article as described herein above, wherein the layered catalyst article is located downstream of an internal combustion engine and the platinum group metal based three-way conversion (TWC) catalyst article is located downstream and in flow communication with the three-way conversion (TWC) catalyst article.
[0080] In one embodiment, the platinum group metal-based TWC catalyst article is a conventional catalyst. In one embodiment, the catalyst article disclosed in U.S. Pat. No. 7,758,834 can be used as the TWC catalyst article. The TWC catalyst article is capable of simultaneously treating NOx, hydrocarbons, and CO from the exhaust. An exemplary diagram of an exhaust system is provided in FIG. 2.
[0081] In another embodiment, an exhaust system for an internal combustion engine includes an exhaust duct in fluid communication with the internal combustion engine via an exhaust manifold, a TWC catalyst article (CC1) in the exhaust duct downstream of the internal combustion engine, and a layered catalyst article of the claimed invention (CC2) in the exhaust duct downstream of the intimately bound catalyst.
[0082] In one aspect, the claimed invention also provides a method for treating a gaseous exhaust stream containing hydrocarbons, carbon monoxide, and nitrogen oxides. The method includes contacting the exhaust stream with a catalyst composition, or catalyst article, or exhaust system according to the claimed invention. The terms "exhaust stream," "engine exhaust stream," "exhaust gas stream," and the like refer to any combination of flowing engine effluent gases, which may also contain solid or liquid particulate matter. The stream includes gaseous components, e.g., the exhaust of a lean-burn engine, and the exhaust stream of a lean-burn engine may contain certain non-gaseous components, such as liquid droplets, solid particulates, and the like. The exhaust stream of a lean-burn engine typically includes products of combustion, products of incomplete combustion, oxides of nitrogen, combustible and / or carbonaceous particulate matter (soot), and unreacted oxygen and / or nitrogen. Such terms refer to the downstream effluent of one or more of the other catalyst system components described herein as well.
[0083] In another aspect, the claimed invention also provides a method for reducing the levels of hydrocarbons, carbon monoxide, and nitrogen oxides in a gaseous exhaust stream, the method comprising contacting the gaseous exhaust stream with a catalyst composition, or catalyst article, or exhaust system according to the claimed invention to reduce the levels of hydrocarbons, carbon monoxide, and nitrogen oxides in the exhaust gas.
[0084] In one aspect, the claimed invention also provides the use of a catalyst composition or catalyst article for purifying a gaseous exhaust stream containing hydrocarbons, carbon monoxide, and nitrogen oxides.
[0085] In some embodiments, the catalytic article converts hydrocarbons to carbon dioxide and water. In some embodiments, the catalytic article converts at least about 60%, or at least about 70%, or at least about 75%, or at least about 80%, or at least about 90%, or at least about 95% of the amount of hydrocarbons present in the exhaust gas stream prior to contact with the catalytic article. In some embodiments, the catalytic article converts carbon monoxide to carbon dioxide. In some embodiments, the catalytic article converts at least about 60%, or at least about 70%, or at least about 75%, or at least about 80%, or at least about 90%, or at least about 95% of the amount of carbon monoxide present in the exhaust gas stream prior to contact with the catalytic article. In some embodiments, the catalytic article converts nitrogen oxides to nitrogen.
[0086] In some embodiments, the catalytic article converts at least about 60%, or at least about 70%, or at least about 75%, or at least about 80%, or at least about 90%, or at least about 95% of the amount of nitrogen oxides present in the exhaust gas stream prior to contact with the catalytic article. In some embodiments, the catalytic article converts at least about 50%, or at least about 60%, or at least about 70%, or at least about 80%, or at least about 90%, or at least about 95% of the total combined amount of hydrocarbons, carbon dioxide, and nitrogen oxides present in the exhaust gas stream prior to contact with the catalytic article. EXAMPLES
[0087] Aspects of the present invention are more fully illustrated by the following examples, which are set forth to illustrate certain specific aspects of the invention and should not be construed as limiting thereof.
[0088] Example 1: Preparation of Upstream TWC Catalyst 1 (PGM only, out of scope) An upstream TWC catalyst with a three-layer washcoat structure was prepared according to Example 1 of U.S. Patent No. 7,758,834. The catalyst was coated on a cylindrical cordierite monolith substrate with a cell density of 600 cpsi (cells per square inch) and a wall thickness of 3 mils (about 100 μm). The total PGM loading was 200 g / ft 3 (Pt / Pd / Rh=0 / 186 / 14).
[0089] Example 2: Preparation of downstream layered catalyst 2 (PGM+non-PGM, inventive catalyst) Non-PGM bottom layer and 1g / ft 3 A downstream catalyst was prepared, comprising a PGM top layer with a PGM loading of (Pt / Pd / Rh=0 / 0 / 1). The catalyst was coated onto a cylindrical monolith cordierite substrate with a cell density of 600 cpsi and a wall thickness of 3 mils. The detailed process is provided below.
[0090] Preparation of bottom layer (non-PGM layer): Approximately 41.3 wt.% high surface area ceria, nickel nitrate (impregnated into the ceria) yielding 2.2 wt.% NiO, 41.3 wt.% high surface area lanthana stabilized zirconia, 2.2 wt.% Fe 2O3 A slurry mixture containing iron(III) nitrate yielding 1.0 wt.% NiO powder (impregnated into lanthana-stabilized zirconia), 11.0 wt.% NiO powder, and zirconium acetate yielding 2.0 wt.% ZrO was coated onto the substrate. The washcoat loading of the bottom layer after calcination at 550 °C for 1 h in air was approximately 2.30 g / in. 3 It was.
[0091] Preparation of the top layer (PGM layer): 50 wt% of the total Rh in the form of rhodium nitrate was impregnated into a stabilized ceria-zirconia composite and the remaining 50 wt% of the total Rh in the form of rhodium nitrate was impregnated into refractory γ-Al2O3. A slurry containing about 32.5 wt% refractory γ-Al2O3, 32.5 wt% stabilized ceria-zirconia composite with approximately 40 wt% ceria, 32.5 wt% high surface area lanthana-stabilized zirconia, a colloidal alumina dispersion yielding 2.4 wt% Al2O3, and 0.047 wt% Rh was coated over the entire bottom layer. The washcoat loading of the top layer after calcination in air at 550 °C for 1 hour was about 1.23 g / in 3 It was.
[0092] Example 3: Preparation of downstream layered catalyst 3 (CuO present, out of scope) 1g / ft 3 The downstream catalyst with a PGM loading of (Pt / Pd / Rh=0 / 0 / 1) was prepared as catalyst 2, except that 1.0 wt % CuO in the form of copper nitrate was added to the bottom layer.
[0093] Example 4: Preparation of downstream layered catalyst 4 (PGM only, out of scope) Two-layer washcoat construction and 20g / ft 3 A downstream TWC catalyst was prepared with a PGM loading of (Pt / Pd / Rh=0 / 16 / 4). The catalyst was coated on a cylindrical monolith cordierite substrate with a cell density of 600 cpsi and a wall thickness of 3 mils. The detailed process is provided below.
[0094] Bottom layer preparation: 100 wt% of the total Pd in the form of palladium nitrate was added to the bottom coat slurry. A slurry containing about 21.0 wt% refractory γ-Al2O3, 70.4 wt% stabilized ceria-zirconia composite with approximately 30 wt% ceria, barium acetate yielding 4.9 wt% BaO, zirconium acetate yielding 2.4 wt% ZrO2, lanthanum nitrate yielding 0.9 wt% La2O3, and 0.45 wt% Pd was coated onto the substrate. The bottom washcoat loading after calcination at 550 °C for 1 hour in air was about 2.06 g / in 3 It was.
[0095] Top layer preparation: 100 wt% of the total Rh in the form of rhodium nitrate was impregnated into the stabilized ceria-zirconia. A slurry containing about 31.2 wt% refractory γ-Al2O3, 62.4 wt% stabilized ceria-zirconia composite with approximately 10 wt% ceria, barium acetate yielding 3.1 wt% BaO, zirconium acetate yielding 3.1 wt% ZrO2, and 0.14 wt% Rh was coated over the entire bottom layer. The washcoat loading of the top layer after calcination at 550 °C for 1 hour in air was about 1.60 g / in 3 It was.
[0096] Testing catalysts 1-4 The monolith catalysts were individually mounted in steel converter cans and aged in the exhaust line of a gasoline engine under a fuel cut aging cycle. The upstream TWC catalyst (catalyst 1) was aged for 50 hours at a maximum bed temperature of 950°C. The downstream catalysts (catalysts 2-4) were aged for 50 hours at a maximum bed temperature of 940°C. The aged catalysts were tested in a SULEV (ultra-low emission vehicle) equipped with a 1.6L turbocharged gasoline engine operated under the US FTP-75 driving cycle according to a validated procedure. The emission control systems (Examples 5-7) contained catalyst 1 (CC1) in the first closely coupled position as the universal upstream TWC catalyst, and the downstream catalyst (catalyst 2 or 3 or 4) (CC2) in the second closely coupled position. The total amount of nitrogen oxides, hydrocarbons, and carbon monoxide at the tailpipe was measured by collecting three bags, and the weight average was calculated. Table 1 shows the NO emissions in the FTP-75 test. x The data provide tailpipe emissions of diesel, THC (total hydrocarbons), and CO.
[0097] Example 5 shows a comparison of the conventional upstream TWC (Catalyst 1) and the 1 g / ft 3 Example 5 contained a PGM-non-PGM catalyst (Catalyst 2) with a PGM loading of 20 g / ft 3 Example 5 exhibited comparable NOx and THC performance to Example 7, which contained a conventional downstream TWC (Catalyst 4) with a PGM loading of 1000 ppm. Example 5 showed better CO performance than Example 7, which is attributed to the presence of NiO component in the bottom layer of Catalyst 2 for the water-gas shift reaction (WGSR). Significant PGM reduction was achieved with Catalyst 2 compared to Catalyst 4. Example 6 contained the same conventional upstream TWC (Catalyst 1) and a PGM-non-PGM catalyst (Catalyst 3) with 1% CuO added in the bottom layer. Example 6 performed poorly in NOx and THC compared to Examples 5 and 7. Analysis of Catalyst 3 revealed that CuO from the bottom layer migrated to the PGM-containing top layer upon aging. The migrated CuO likely sequestered the PGM function.
[0098] [Table 1]
[0099] Example 8: Preparation of Layered Upstream TWC Catalyst 5 (PGM only, out of scope) Two-layer washcoat construction and 142g / ft 3 An upstream TWC catalyst was prepared with a PGM loading of (Pt / Pd / Rh=0 / 137 / 5). The catalyst was coated on a cylindrical monolith cordierite substrate with a cell density of 600 cpsi and a wall thickness of 3 mils. The detailed process is provided below.
[0100] Preparation of bottom layer: 36 wt% of the total Pd in the form of palladium nitrate was impregnated onto a stabilized ceria-zirconia composite, and 54 wt% of the total Pd in the form of palladium nitrate was impregnated onto a refractory γ-Al2O3. A slurry containing about 25.3 wt% refractory γ-Al2O3, 63.3 wt% stabilized ceria-zirconia composite with approximately 40 wt% ceria, barium acetate yielding 6.3 wt% BaO, a colloidal alumina dispersion yielding 2.1 wt% Al2O3, and 3.0 wt% Pd was coated onto a substrate. The washcoat loading of the bottom layer after calcination in air at 550 °C for 1 hour was about 2.37 g / in 3 It was.
[0101] Preparation of the top layer: 10 wt% of the total Pd in the form of palladium nitrate was impregnated onto a stabilized ceria-zirconia composite, and 100 wt% of the total Rh in the form of rhodium nitrate was impregnated onto a refractory γ-Al2O3. A slurry mixture containing about 73.5 wt% refractory γ-Al2O3, 21.2 wt% stabilized ceria-zirconia composite with approximately 40 wt% ceria, neodymium nitrate yielding 1.8 wt% Nd2O3, a colloidal alumina dispersion yielding 2.6 wt% Al2O3, 0.58 wt% Pd, and 0.21 wt% Rh was coated onto the entire bottom layer. The washcoat loading of the top layer after calcination in air at 550 °C for 1 hour was about 1.36 g / in 3 It was.
[0102] Example 9: Preparation of downstream layered catalyst 6 (PGM+non-PGM, inventive catalyst) Non-PGM bottom layer and 1g / ft 3 A downstream catalyst was prepared, comprising a PGM top layer with a PGM loading of (Pt / Pd / Rh=0 / 0 / 1). The catalyst was coated onto a cylindrical monolith cordierite substrate with a cell density of 600 cpsi and a wall thickness of 3 mils. The detailed process is provided below.
[0103] Preparation of bottom layer (non-PGM layer): A slurry containing about 60.6 wt.% high surface area ceria, 20.2 wt.% NiO powder, nickel nitrate yielding 15.2 wt.% NiO, zirconium acetate yielding 2.0 wt.% ZrO, and a colloidal alumina dispersion yielding 2.0 wt.% AlO was coated onto the substrate. The washcoat loading of the bottom layer after calcination at 550 °C for 1 hour in air was about 2.97 g / in. 3 It was.
[0104] Preparation of the top layer (PGM layer): 50 wt% of the total Rh in the form of rhodium nitrate was impregnated into a stabilized ceria-zirconia composite and the other 50 wt% of the total Rh in the form of rhodium nitrate was impregnated into a refractory γ-Al2O3. A slurry containing about 30.8 wt% refractory γ-Al2O3, 61.6 wt% stabilized ceria-zirconia composite with approximately 22 wt% ceria, zirconium acetate yielding 3.8 wt% ZrO2, colloidal alumina dispersion yielding 3.8 wt% Al2O3, and 0.045 wt% Rh was coated over the entire bottom layer. The washcoat loading of the top layer after calcination in air at 550 °C for 1 hour was about 1.30 g / in 3 It was.
[0105] Example 10: Preparation of downstream layered TWC catalyst 7 (PGM only, out of scope) A downstream TWC catalyst with a two-layer washcoat structure was prepared. Catalyst 7 had a washcoat coating capacity of 14 g / ft 3 Catalyst 7 has the same formulation as catalyst 5, except that it has a PGM loading of (Pt / Pd / Rh=0 / 12 / 2).
[0106] Testing catalysts 5-7 The monolith catalysts were individually mounted in steel converter cans and aged in the exhaust line of a gasoline engine under an exothermic aging cycle. The upstream TWC catalyst (catalyst 5) was aged for 100 hours at a maximum bed temperature of 1050°C. The downstream catalysts (catalysts 6 and 7) were aged for 100 hours at a maximum bed temperature of 950°C. The aged catalysts were tested in a SULEV vehicle equipped with a 2L turbocharged gasoline engine operated under the US FTP-75 driving cycle according to a validated procedure. The emission control system (Examples 11-12) contained catalyst 5 (CC) in a close-coupled position as a universal upstream TWC catalyst, and downstream catalyst (UF) in an underbed position. The total amounts of nitrogen oxides, hydrocarbons, and carbon monoxide at the tailpipe were measured by collecting three bags, and the weight average was calculated. Table 2 shows the NO emissions in the FTP-75 test. x The in-house study provides tailpipe emissions of EV, THC, and CO.
[0107] Example 11 shows a conventional upstream TWC (Catalyst 5) and a 1 g / ft 3 Example 11 contained a PGM-non-PGM hybrid catalyst (Catalyst 6) with a PGM loading of 14 g / ft and a high NiO content. Example 12 contained the same conventional upstream TWC (Catalyst 5) and a 14 g / ft 3 Example 11 exhibited similar NOx performance to Example 12, which contained a conventional downstream TWC (Catalyst 7) with a PGM loading of 1.0. Example 11 exhibited better THC and CO performance than Example 12.
[0108] [Table 2]
[0109] Example 13: Preparation of upstream layered catalyst 8 (PGM+non-PGM, inventive catalyst) Non-PGM bottom layer and 51g / ft 3An upstream catalyst was prepared that included a PGM top layer with a PGM loading of (Pt / Pd / Rh=0 / 50 / 1). The catalyst was coated onto a cylindrical cordierite monolith substrate with a cell density of 600 cpsi and a wall thickness of 3 mils.
[0110] Preparation of bottom layer (non-PGM layer): A slurry containing about 60.6 wt.% high surface area ceria, 20.2 wt.% NiO powder, nickel nitrate yielding 15.2 wt.% NiO, zirconium acetate yielding 2.0 wt.% ZrO, and a colloidal alumina dispersion yielding 2.0 wt.% AlO was coated onto the substrate. The washcoat loading of the bottom layer after calcination at 550 °C for 1 hour in air was about 2.97 g / in. 3 The detailed process is provided below.
[0111] Preparation of the top layer (PGM layer): 100 wt. % of the total Pd in the form of palladium nitrate was impregnated onto a stabilized ceria-zirconia composite, and 100 wt. % of the total Rh in the form of rhodium nitrate was impregnated onto a refractory γ-Al2O3. A slurry containing about 30.1 wt. % refractory γ-Al2O3, 61.2 wt. % stabilized ceria-zirconia composite with approximately 22 wt. % ceria, zirconium acetate yielding 3.7 wt. % ZrO2, colloidal alumina dispersion yielding 3.7 wt. % Al2O3, 2.2 wt. % Pd, and 0.044 wt. % Rh was coated onto the entire bottom layer. The washcoat loading of the top layer after calcination in air at 550 °C for 1 hour was about 1.33 g / in 3 It was.
[0112] Example 14: Preparation of Upstream Layered TWC Catalyst 9 (PGM only, out of scope) An upstream TWC catalyst with a two-layer washcoat structure was prepared. Catalyst 9 had a washcoat content of 144 g / ft 3 Catalyst 9 has the same formulation as catalyst 5, except that it has a PGM loading of (Pt / Pd / Rh=0 / 140 / 4).
[0113] Testing of catalysts 8 and 9 The monolith catalysts were individually mounted in steel converter cans and aged in the exhaust line of a gasoline engine under an exothermic aging cycle. The examples were aged for 100 hours at a maximum bed temperature of 1050°C. The aged catalysts were tested in a PZEV vehicle (Partial Zero Emission Vehicle) with a 2L gasoline engine operated under the US FTP-75 driving cycle according to a validated procedure. The emission control system (Examples 13-14) contained a single catalyst (CC) in a closely coupled position. The total amounts of nitrogen oxides, hydrocarbons, and carbon monoxide at the tailpipe were measured by collecting three bags and the weight average was calculated. Table 3 shows the NO emissions in the FTP-75 test. x The in-house study provides tailpipe emissions of EV, THC, and CO.
[0114] 144g / ft 3 compared to a conventional upstream TWC (catalyst 9) with a PGM loading of 51g / ft 3 The inventive catalyst (Catalyst 8) with a PGM loading of 100% demonstrated improved NOx and CO reduction. Significant PGM reduction was achieved with Catalyst 8 compared to Catalyst 9.
[0115] [Table 3]
[0116] References throughout this specification to "one embodiment," "a particular embodiment," "one or more embodiments," or "an embodiment" mean that a particular feature, structure, material, or characteristic described in connection with the embodiment is included in at least one embodiment of the claimed invention. Thus, phrases such as "in one or more embodiments," "in a particular embodiment," "in some embodiments," "in one embodiment," or "in one embodiment" appearing in various places throughout this specification do not necessarily refer to the same embodiment of the claimed invention. Furthermore, in one or more embodiments, particular features, structures, materials, or characteristics may be combined in any suitable manner. All of the various embodiments, aspects, and options disclosed herein may be combined in all variations, regardless of whether such features or elements are expressly combined in the description of a particular embodiment herein. The claimed invention, in any of its various aspects and embodiments, is intended to be read as a whole such that any separable features or elements of the disclosed invention should be considered as intended to be combinable unless the context clearly dictates otherwise.
[0117] Although the embodiments disclosed herein have been described with reference to specific embodiments, it should be understood that these embodiments are merely illustrative of the principles and applications of the claimed invention. It will be apparent to those skilled in the art that various modifications and variations can be made to the method and apparatus of the claimed invention without departing from the spirit and scope of the claimed invention. Therefore, the claimed invention is intended to include modifications and variations within the scope of the appended claims, their equivalents, and the above embodiments are presented for purposes of illustration and not limitation.
Claims
1. 1. A layered catalyst article for treating a gaseous exhaust stream containing hydrocarbons, carbon monoxide, and nitrogen oxides, comprising: a) a first layer comprising a nickel component supported on a ceria component, the amount of said nickel component being 1.0 to 50 wt. %, calculated as nickel oxide, based on a total weight of said first layer, and said first layer being essentially free of copper, the amount of said copper being <0.001 wt. %; b) a second layer comprising an oxygen storage component and a platinum group metal component supported on an alumina component, the platinum group metal component comprising platinum, rhodium, palladium, or any combination thereof, the amount of the platinum group metal component being 0.01 to 5 wt. %, based on the total weight of the second layer; and c) a substrate, wherein the first layer is deposited as a bottom layer on the substrate and the second layer is deposited as a top layer on the first layer; and the oxygen storage component comprises ceria-zirconia, ceria-zirconia-lanthana, ceria-zirconia-yttria, ceria-zirconia-lanthana-yttria, ceria-zirconia-neodymia, ceria-zirconia-praseodymia, ceria-zirconia-lanthana-neodymia, ceria-zirconia-lanthana-praseodymia, ceria-zirconia-lanthana-neodymia-praseodymia, or any combination thereof, the amount of the alumina component is 20 to 80 wt %, based on the total weight of the second layer, the alumina component comprises alumina, lanthana-alumina, ceria-alumina, ceria-zirconia-alumina, zirconia-alumina, lanthana-zirconia-alumina, baria-alumina, baria-lanthana-alumina, baria-lanthana-neodymia-alumina, or combinations thereof, the amount of the alumina component is 10 to 80 wt %, based on the total weight of the second layer; and A layered catalyst article, wherein at least one of the first and second layers comprises a zone arrangement including a first zone and a second zone, and the first or second zone spans 45-90% of the length of the substrate.
2. 10. The layered catalyst article of claim 1, wherein the amount of said nickel component of said first layer is from 10 to 40 weight percent, calculated as nickel oxide, based on the total weight of said first layer.
3. 3. The layered catalyst article of claim 1 or 2, wherein the ceria component of the first layer comprises a dopant selected from zirconia, yttria, praseodymia, lanthana, neodymia, samaria, gadolinia, alumina, titania, baria, strontia, and combinations thereof, and the amount of the dopant is 1.0 to 20 wt %, based on the total weight of the ceria component.
4. 4. The layered catalyst article of claim 1, wherein the first layer comprises a transition metal selected from manganese, iron, zinc, and combinations thereof, and the amount of the transition metal is 1.0 to 10 wt. %, calculated as the corresponding transition metal oxide, based on the total weight of the first layer.
5. 5. The layered catalyst article of claim 4, wherein said transition metal is iron and the amount of said iron, calculated as iron oxide, is from 1.0 to 10 weight percent based on the total weight of said first layer.
6. The layered catalyst article of any of claims 1 to 5, wherein the amount of said platinum group metal component in said second layer is from 0.02 to 1.0 weight percent, based on the total weight of said second layer.
7. 7. The layered catalyst article of any of claims 1 to 6, wherein the platinum group metal component comprises i) 0.02 to 1 wt. % rhodium, based on the total weight of the second layer, or ii) palladium and rhodium, or iii) platinum and rhodium, and in ii) or iii) the ratio of palladium or platinum to rhodium is in the range of 100:1 to 1:
5.
8. 8. The layered catalyst article of any of claims 1 to 7, wherein the ceria content of the oxygen storage component of the second layer ranges from 5 to 50 weight percent, based on the total weight of the oxygen storage component.
9. 9. The layered catalyst article of any of claims 1 to 8, wherein the second layer comprises at least one alkaline earth metal oxide comprising barium oxide, strontium oxide, or any combination thereof, and the amount of the alkaline earth metal oxide is from 1 to 20 wt.%, based on the total weight of the second layer.
10. The layered catalyst article of any of claims 1 to 9, wherein the substrate comprises a flow-through ceramic honeycomb structure, a wall-flow ceramic honeycomb structure, or a metal honeycomb structure.
11. 11. A process for preparing a layered catalyst article according to any of claims 1 to 10, comprising: preparing a bottom layer slurry; depositing the bottom layer slurry on a substrate to obtain a bottom layer; preparing a top layer slurry; depositing the top layer slurry on the bottom layer to obtain a top layer, followed by calcination at a temperature in the range of 400 to 700°C, wherein the step of preparing the bottom layer slurry or the top layer slurry comprises a technique selected from incipient wetness impregnation, incipient wetness co-impregnation, and post-addition.
12. 11. An exhaust system for an internal combustion engine, said system comprising: i) a catalyst article of the layered catalyst article of any one of claims 1 to 10; and ii) optionally a layered catalyst article of 1766 to 10595 g / m2 selected from platinum, palladium, rhodium, and combinations thereof. 3 (50~300g / ft 3 and a platinum group metal based three-way conversion (TWC) catalyst article comprising a platinum group metal of the formula:
13. 13. The exhaust system of claim 12, wherein the system comprises a platinum group metal based three-way conversion (TWC) catalyst article and the layered catalyst article of any of claims 1-10, wherein the platinum group metal based three-way conversion (TWC) catalyst article is located downstream of an internal combustion engine, and the layered catalyst article is located downstream in flow communication with the platinum group metal based three-way conversion (TWC) catalyst article.
14. 13. The exhaust system of claim 12, wherein the system comprises a platinum group metal based three-way conversion (TWC) catalyst article and the layered catalyst article of any of claims 1-10, the layered catalyst article being located downstream of an internal combustion engine, and the platinum group metal based three-way conversion (TWC) catalyst article being located downstream in flow communication with the layered catalyst article.
15. 15. A method for reducing the levels of hydrocarbons, carbon monoxide, and nitrogen oxides in a gaseous exhaust stream, comprising contacting the gaseous exhaust stream with a layered catalyst article according to any one of claims 1-10, or an exhaust system according to any one of claims 12-14, to reduce the levels of hydrocarbons, carbon monoxide, and nitrogen oxides in the gaseous exhaust stream.
16. Use of the layered catalyst article of any one of claims 1 to 10 for purifying a gaseous exhaust stream comprising hydrocarbons, carbon monoxide and nitrogen oxides.
Citation Information
Patent Citations
Base Metal Oxide Promoted Rhodium-Containing Catalyst Compositions
JP1994504940A
Exhaust gas purifying catalyst
JP2014144426A